2010
DOI: 10.1042/bj20091077
|View full text |Cite
|
Sign up to set email alerts
|

Induced, selective proteolysis of MLK3 negatively regulates MLK3/JNK signalling

Abstract: MLK3 (mixed lineage kinase 3) is a MAP3K [MAPK (mitogen-activated protein kinase) kinase kinase] that activates multiple MAPK pathways, including the JNK (c-Jun N-terminal kinase) pathway. Immunoblotting of lysates from cells ectopically expressing active MLK3 revealed an additional immunoreactive band corresponding to a CTF (C-terminal fragment) of MLK3. In the present paper we provide evidence that MLK3 undergoes proteolysis to generate a stable CTF in response to different stimuli, including PMA and TNFalph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…This cleavage produces a C-terminal fragment that heterodimerizes with full-length MLK3 and reduces MLK3 activation loop phosphorylation and MLK3-dependent activation of JNK. Furthermore, production of the C-terminal fragment is blocked by proteasome inhibition (52). A previous study by Gonda et al showed that the Drosophila melanogaster MLK Slipper (Slpr) is phosphorylated in response to heat stress on a serine that is within a MAPK PXSP consensus sequence (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cleavage produces a C-terminal fragment that heterodimerizes with full-length MLK3 and reduces MLK3 activation loop phosphorylation and MLK3-dependent activation of JNK. Furthermore, production of the C-terminal fragment is blocked by proteasome inhibition (52). A previous study by Gonda et al showed that the Drosophila melanogaster MLK Slipper (Slpr) is phosphorylated in response to heat stress on a serine that is within a MAPK PXSP consensus sequence (53).…”
Section: Discussionmentioning
confidence: 99%
“…(C) Reactions and immunoblotting were carried out as described above for panel A with the following E2 enzymes: UbcH5a, -b, -c, and -d; Ubc13/Uev1a plus Ube2W (13/2W); Ubc13/Uev1a plus Cdc34 (13/Cdc34); UbcH8; and UbcH9. enous MLK3 undergoes proteolytic cleavage at a site within the kinase domain in response to phorbol-12-myristate-13-acetate (PMA) and TNF (52). This cleavage produces a C-terminal fragment that heterodimerizes with full-length MLK3 and reduces MLK3 activation loop phosphorylation and MLK3-dependent activation of JNK.…”
Section: Discussionmentioning
confidence: 99%
“…MLK3, also known as MAP3K11, Src-homology 3 (SH3) domain-containing proline-rich kinase (SPRK), protein-tyrosine kinase 1 (PTK1), and slipper ( Drosophila ), was first identified in 1994 [ 11 , 14 , 15 ]. This 847-amino acid protein is the only member in the MLK subfamily that has been extensively studied in terms of regulation, functions and implications in human diseases [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. MLK3, as its name MAP3K11 implies, functions as a MAP3K to phosphorylate and activate specific MAP2Ks, which in turn activate specific MAPKs.…”
Section: Mlk3mentioning
confidence: 99%
“…These mechanisms include relief of inhibition, dimerization, posttranslational modification, scaffolding, proteolysis, and changes in subcellular localization [40], [41], [42], [43], [44]. In one instance, mammalian MLK3 is phosphorylated by JNK as a means of positive feedback [42].…”
Section: Introductionmentioning
confidence: 99%